Contribution of chloride ions to the sulfidization flotation of cerussite. (November 2015) - Feng, Qicheng; Wen, Shuming; Zhao, Wenjuan; Wang, Yijie; Cui, Chuanfa
Highlights: The number of active sites on the mineral surface is increased by the addition of chloride ions. Chloride ions significantly improve the cerussite sulfidization. More lead sulfide species form on the mineral surface with chloride ions. The flotation recovery of cerussite is greatly increased with chloride ions. Abstract: The effect of the addition of chloride ions on the sulfidization flotation of cerussite was investigated by micro-flotation tests, surface adsorption experiments, zeta potential measurements, and X-ray photoelectron spectroscopy (XPS) analysis. The micro-flotation test results indicated that the addition of chloride ions prior to sulfidization significantly increased the flotation recovery of cerussite. The maximum and minimum percentages of increase in flotation recovery were 16.63% and 10.51%, respectively. Surface adsorption experiments of sulfide demonstrated that there was a higher adsorption concentration of S species on the mineral surface, and its adsorption efficiency was enhanced. The results of zeta potential measurements revealed that the addition of Na2 S and chloride ions to the solution caused a more negative zeta potential than the addition of Na2 S alone. The XPS analysis results indicated that more lead sulfide formed on the mineral surface after the addition of chloride ions into the pulp solution. These results consistently showed that the addition of chloride ions played a significant role in the sulfidization of cerussite, resulting in a better flotation performance.